Workload, incentives, and job satisfaction: Their influence on employee retention - Aris Prihantoro; Sutianingsih (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to analyze the effect of workload, incentives, and job satisfaction on employee retention. Methodology: The data collection method used a questionnaire conducted on respondents, namely employees of UD. Agung Rejeki with a saturated sampling technique. The data analysis technique in testing the research hypothesis used linear and multiple regression analysis techniques and the Sobel Test. Results: 1) there is a positive and significant effect between workload variables on employee retention; 2) there is a positive and significant effect between incentives on employee retention; 3) there is a negative effect between workload on job satisfaction; 4) there is a positive and significant effect between incentives on job satisfaction; 5) there is a positive and significant effect between workload, incentives, and job satisfaction on employee retention; 6) job satisfaction is able to mediate the relationship between workload and employee retention; 7) job satisfaction is able to mediate the relationship between incentives and employee retention. Conclusions: This study found that workload and incentives have a positive and significant influence on employee retention. However, workload has a negative impact on job satisfaction, while incentives actually increase job satisfaction. In addition, job satisfaction itself has been proven to have a positive and significant effect on employee retention. Job satisfaction also acts as a mediator in the relationship between workload and employee retention, as well as between employee incentives and retention. This shows that to increase employee retention, companies need to pay attention to workload and provide adequate incentives to maintain job satisfaction levels. Limitations: The study was limited to companies in Lampung, the potential for questionnaire bias, the approach was only quantitative, and did not consider external factors such as organizational culture and leadership. Contribution: This research reinforces the importance of implementing GHRM in improving employee performance and organizational sustainability, as well as encouraging follow-up research with qualitative approaches and external factors.